FAULT SEAL ANALYSIS AT SAKTI FIELD, KUTEI BASIN, EAST KALIMANTAN - DWI IKHWAN, AULIA
Sakti Field is a productive gas field which operated by PT.Pertamina Hulu Mahakam. Sakti Field is located in the southern of Kutei Basin consisting delta front – prodelta sediment which part of Sepinggan Deltaic Series with distributary mouth bar sandstones reservoir and controlled by en echelon normal faults that could be hydrocarbon traps if they are capable of being sealed. The purpose of this research is to analyze properties and characteristics of normal faults of Sakti Field. Shale Gouge Ratio (SGR) method is used to analyze that faults properties and characteristics. 3D seismic data and well data with final well reports and Modular Dynamic Tester (MDT) result report are used in this research. This research focused on Sepinggan Deltaic Sequence interval as hydrocarbon interval. Analysis include making juxtaposition maps, volume of shale (Vsh) in faults plane, SGR maps, and permeability maps in fault plane. Results of analysis showed that faults plane were dominated by sandstones-shales and shales-shales juxtaposition with variation of throw values around 0 – 150 meters and volume of shales in faults plane around 50 – 95 %. SGR values around 30 – 95% and permeability values in faults plane around 0,0001 mD – 0,1 mD. Cut-off value of SGR to determine whether faults are sealing or not is 30%, using callibration between SGR values and MDT data. Results of this research showed that normal faults in Sakti Field are sealing faults and could become potential hydrocarbon traps. Controlling factors that affect SGR values are shales smears process and domination of sandstones-shales and shales-shales juxtaposition. The controlling factors are influenced by lithology, which is dominated by shales with thin sandstones reservoir.